2003
DOI: 10.1183/09031936.03.00025303
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and dietary energy restriction in stable chronic obstructive pulmonary disease patients

Abstract: Tumour necrosis factor (TNF)-a has been found to be increased in malnourished chronic obstructive pulmonary disease (COPD) patients; however, the main cause of this phenomenon remains undetermined. In normal subjects, TNF-a production may be induced by dietary energy deprivation. The aim of this study was to investigate if stable COPD patients present alterations of inflammatory mediators after 48 h of dietary energy restriction.Fourteen COPD patients were admitted to the hospital while receiving an experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 25 publications
(48 reference statements)
1
20
0
3
Order By: Relevance
“…IL-6 is also increased in the plasma of COPD patients (Debigare et al, 2003;Godoy et al, 2003;Hageman et al, 2003), especially during exacerbations (Wedzicha et al, 2000). Monocytes from COPD patients release more IL-6 in response to stimulation with LPS than cells from normal subjects (Aldonyte et al, 2003).…”
Section: Interleukin-6mentioning
confidence: 99%
“…IL-6 is also increased in the plasma of COPD patients (Debigare et al, 2003;Godoy et al, 2003;Hageman et al, 2003), especially during exacerbations (Wedzicha et al, 2000). Monocytes from COPD patients release more IL-6 in response to stimulation with LPS than cells from normal subjects (Aldonyte et al, 2003).…”
Section: Interleukin-6mentioning
confidence: 99%
“…Interestingly, in diseases of increased diaphragmatic loading, such as COPD, increased plasma cytokine levels have been documented [47][48][49][50]. Although, initially, these cytokines had been attributed to the bronchial inflammation that accompanies COPD, recent data have shown different regulation of the cytokine response in induced sputum and plasma [47], which suggests that plasma cytokinemia in COPD is not due to an overflow of inflammatory mediators from the local lung compartment.…”
Section: Systemic Effectsmentioning
confidence: 99%
“…Some of the data prove a significant increase in the blood's proinflammatory cytokine level in COPD accompanied by a significant increase in air way resistance [6][7][8]13]. It has been shown that this increase is not connected to an increase in the blood of cytokine levels caused by their release from inflamma tion foci located in the respiratory system.…”
Section: Immune Response To Inspiratory Resistive Loadmentioning
confidence: 98%
“…Current experimental and clinical studies show an increase in the cytokine concentration in the blood plasma and respiratory muscles in the illness of the respiratory system accompanied by an increase in the resistance to breathing and also in healthy subjects during breathing with an additional inspiratory resis tive load [6][7][8][9][10][11]. A new concept has been developed based on these data.…”
mentioning
confidence: 99%